2022
DOI: 10.1093/mnras/stac2851
|View full text |Cite
|
Sign up to set email alerts
|

Orientation effects on cool gas absorption from gravitational-arc tomography of a z = 0.77 disc galaxy

Abstract: We use spatially-resolved spectroscopy of a distant giant gravitational arc to test orientation effects on Mg ii absorption equivalent width (EW) and covering fraction (〈κ〉) in the circumgalactic medium of a foreground star-forming galaxy (G1) at z ∼ 0.77. Forty-two spatially-binned arc positions uniformly sample impact parameters (D) to G1 between 10 and 30 kpc and azimuthal angles α between 30○ and 90○ (minor axis). We find an EW-D anti-correlation, akin to that observed statistically in quasar absorber stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Previous works (e.g., Schroetter et al 2019) found a segregation of absorbers along the galaxy minor and major axis, suggesting that the cool CGM could be described by a wind plus disk model. In particular, Fernandez-Figueroa et al (2022) found a dependence of the EW strength on the azimuthal angle for one of the three MUSE fields analyzed in this work, SGAS J1226+2152, although the effect is diluted when considering the three fields together, as we see in Sect. 2.4.…”
Section: Limitations and Assumptions Of This Studymentioning
confidence: 54%
See 2 more Smart Citations
“…Previous works (e.g., Schroetter et al 2019) found a segregation of absorbers along the galaxy minor and major axis, suggesting that the cool CGM could be described by a wind plus disk model. In particular, Fernandez-Figueroa et al (2022) found a dependence of the EW strength on the azimuthal angle for one of the three MUSE fields analyzed in this work, SGAS J1226+2152, although the effect is diluted when considering the three fields together, as we see in Sect. 2.4.…”
Section: Limitations and Assumptions Of This Studymentioning
confidence: 54%
“…Only successful fits are considered. Also, as we are using an updated selection criterion, these maps are different from those in Lopez et al (2018Lopez et al ( , 2020 and (Fernandez-Figueroa et al 2022).…”
Section: Automated Absorption Line Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have confirmed the need for a multiphase CGM but have not been able, given the sparseness of background sources, to directly probe the detailed morphology and physical properties (such as the density and 'clumpiness') of the CGM. This limitation can partly be mitigated by using lensed background quasars which afford multiple sight lines through one halo's CGM (Smette et al 1992 ;Monier, Turnshek & Lupie 1998 ;Rauch et al 2001 ;Ellison et al 2004 ;Zahedy et al 2016 ;Rubin et al 2018 ) or gravitational arc tomography (Lopez et al 2018 ;Mortensen et al 2021 ;Tejos et al 2021 ;Bordoloi et al 2022 ;Fernandez-Figueroa et al 2022 ). The situation has changed in recent years due to new, highly sensitive instrumentation, such as the Multi-Unit Spectroscopic Explorer (MUSE) on the ESO Very Large Telescope (VLT) (Bacon et al 2010 ) and the Keck Cosmic Web Imager (KCWI) (Martin et al 2010 ;Morrissey et al 2018 ) which can reach sensitivity levels that are at least one order of magnitude deeper than previously possible.…”
Section: Introductionmentioning
confidence: 99%